IRON ABSORPTION; NATURE, AND NURTURE INTERACTIONS - Sanjiwani, Putu Amrytha; Pratiwi, Dessy; Sitorus, Nova Lidia (Ridwan Institute, 2025)
Background: Iron deficiency anemia (IDA) is a global health concern, particularly affecting women and children. Both genetic and dietary factors contribute to iron absorption and status. Understanding these interactions is vital for effective prevention strategies. Methods: This narrative review examined literature from Scopus-indexed journals (2005–2024) to explore the influence of TMPRSS6 gene polymorphisms—particularly rs855791 and rs4820268—and dietary components (enhancers and inhibitors) on iron absorption. Results: Genetic variations in TMPRSS6, especially rs855791, are associated with increased hepcidin levels, leading to decreased iron absorption and lower hemoglobin. On the dietary side, ascorbic acid and meat proteins significantly enhance non-heme iron uptake, while phytates, polyphenols, and calcium inhibit it. Food processing techniques such as fermentation andgermination can reduce inhibitor effects and improve iron bioavailability. Conclusion: Iron absorption is influenced by both inherited genetic variations and modifiable dietary practices. A combined understanding of these nature and nurture factors is essential to develop personalized and population-based nutritional strategies to prevent and manage IDA effectively